Evaluation of Some common clinical factors in extensive vitiligo- a case control study - Dr. Nirmalya Kumar Das; Suchibrata Das (International Journal of Medical Research and Review, 2019)
Introduction: Vitiligo is a common depigmenting disorder with profound stigma. Prevalence of vitiligo is 0.5% to 1%. Information about association of progressive vitiligo are well known. Prognostic factors of vitiligo also enlisted. However, little information is available on the risk factors for developing extensive vitiligo.Aims and Objectives: Aims of the study was to identify – factors which are associated with extensive vitiligo (involving more than 5% of the body surface area). The following risk factors were evaluated, Onset before 20 years of age, Duration of disease greater than 2 years, Presence of Koebner’s phenomenon, Family history of vitiligo, Presence of leucotrichia and Mucosal involvement.Materials and Methods: A case control study were designed. Patients with Vitiligo > 5% body surface area involvement were classified as cases and <5% body surface area were labeled as controls. The frequency of evaluating associated clinical factors among the cases and controls were used to evaluate the extensive vitiligo’s association with risk factors (disease risk associated exposure).Results: Two hundred and eleven patients were evaluated. The mean age at onset was 19.07+13.51 (+SD) years. Acrofacial vitiligo was the commonest type of vitiligo. Duration of disease more than 2 years, presence of Koebner’s Phenomenon, Family history, Symmetry of lesions, milky white colour of lesion, presence of Leucotrichia, mucosal involvement and Acrofacial type vitiligo had statistically significant (p<.05) association with extensive vitiligo. Ratio of the odds of the outcomes in two groups was noted significant with Duration of disease more than 2 years, Koebner,s Phenomenon, Mucosal involvement and Leucotrichia.Conclusion: This case-control study has demonstrated a weak association between extensive vitiligo and duration of disease greater than 2 years. It has also indicated that koebner’s phenomenon, mucosal involvement and leucotrichia are additional risk factors.